Acute Fatty Liver of Pregnancy in a Taiwanese Tertiary Care Center: A Retrospective Review - Hui-Hsuan Lau; Yi-Yung Chen; Jian-Pei Huang; Chen-Yu Chen; Tsung-Hsien Su; Chie-Pein Chen (Elsevier, 2010)
Objective: To evaluate the demographics, clinical presentations, laboratory findings, and maternal and fetal outcomes in patients with acute fatty liver of pregnancy. Materials and Methods: A retrospective review was conducted of the records of pregnant patients with a diagnosis of acute fatty liver in a tertiary medical center over a 22-year period. Results: Eighteen patients with acute fatty liver of pregnancy were recruited, all of whom developed the disease in the third trimester. Eleven women (61%) were primigravid and four (22%) had twin pregnancies; six (33%) were diagnosed antepartum, and the other 12 (67%) were diagnosed postpartum. There were two maternal deaths (11%) and four fetal deaths (18%). The most common complications apart from severe liver dysfunction were acute renal failure (83%), hypoglycemia (61%), and disseminated intravascular coagulation (61%). Conclusion: Women who become acutely ill during the third trimester of pregnancy should undergo tests for acute fatty liver of pregnancy, including laboratory tests for assessing liver function and coagulation profile.